Non-linear association between extracellular water/total body water ratio and all-cause mortality: a population-based cohort study - Yan Wang; Jie Liu; Huaiyu Hao; Qiang Lu; Lei Zhang; Guimei Wei; Xueyan Shen (Scientific Reports)
Abstract Early extracellular water (ECW) alterations might act as preclinical markers of disease, as these changes often occur in early stages. Quantifying this relationship could provide insights into clinical practice and evaluating nutritional interventions in personalized health. This study examined the association between extracellular water/total body water ratio (ECW/TBW) and all-cause mortality in adults using data from the National Health and Nutrition Examination Survey (1999–2004) and mortality follow-up until 2019. Among 6338 participants, 307 died over 20 years. Kaplan–Meier curves showed higher mortality with elevated ECW/TBW (log-rank P = 0.038). Multivariable Cox models indicated the highest ECW/TBW quartile (≥ 44.6%) had an adjusted HR of 1.60 (95% CI 1.15–2.23; P = 0.005). Restricted cubic spline analysis revealed a J-shaped non-linear relationship (P = 0.009), with an inflection point at 42.4%. Piecewise regression showed an adjusted HR of 1.10 (95% CI 1.05–1.15; P < 0.001) for ECW/TBW ≥ 42.4%. Specifically, each one-unit increase in ECW/TBW beyond the inflection point was associated with a 10% higher risk of all-cause mortality. This suggests ECW/TBW could be a useful marker for risk assessment and guiding interventions.